PERAN GURU DALAM PENGEMBANGAN KURIKULUM DAN PENERAPAN PEMBELAJARAN DI PAUD - Sifa Ulfadilah; Astuti Darmiyanti; Nida’ul Munafiah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
This study aims to find out how the role of teachers in curriculum development and the application of learning in Early ChildhoodEducation Institutions (ECCE). This research method uses literature study research or literature review studies. The result of this study,that the core of the educational program is the curriculum. Policies and approaches aimed at achieving national education goals can beseen as curricula. To ensure that Early Childhood Education (ECCE) is implemented in accordance with the established objectives, it isimportant that all educators and administrators participating in Early Childhood Education (ECCE) have an understanding of the basicsand structure of the Early Childhood Education Curriculum since 2013. The application of learning in the 2013 curriculum emphasizesthe scientific approach is to ensure that students master knowledge and understand various modules by utilizing a scientific approach,meaning that students can independently get the knowledge found from various sources of information. The scientific approach is closelyrelated to scientific methods. Scientific (scientific) methods usually involve observing the necessary activities to formulate hypotheses orcollect data. The scientific method is usually based on the presentation of information obtained through observation or experimentation.Teachers can support scientific approaches during the learning process using a variety of complementary approaches such as storytelling, conversations, assignments, social dramas, demonstrations, tourist works, projects, and experiments. Teachers, students, and learning resources are part of the learning process. Educators plan lessons until students can gain the knowledge, attitudes, and abilities they need to meet future challenges. If a teacher creates daily learning activities that demonstrate the application of a scientific approach, the application of that approach to learning is to be successful. And also an integrated approach to the early childhood curriculum.